Changes in the photosynthetic response of lettuce exposed to toxic element multicontamination under hydroponic conditions - M. LHOTSKÁ; V. ZEMANOVÁ; D. PAVLÍKOVÁ; F. HNILIČKA (Photosynthetica, 2023)
The effect of toxic element multicontamination on photosynthetic responses was observed in a greenhouse hydroponic culture of lettuce plants (Lactuca sativa var. capitata). The experiment focused only on the combined effect of selected toxic elements without the influence of soil, due to the hydroponic conditions. Pre-cultivated (six-true-leaf stage) plants were grown in control and contaminated hydroponic culture for 14 d. The mix of toxic elements (As, Cd, Pb, and Zn) in the contaminated solution corresponded to the water-soluble fraction of soil from the anthropogenically contaminated Litavka River area, Czech Republic. The plant response was measured by determining the toxic element contents, dry biomass, and gas-exchange parameters. Lettuce accumulated toxic elements predominantly in the roots, with low translocation to the leaves. The uptake of toxic elements harmed photosynthesis and caused a decrease in net photosynthetic rate, transpiration rate, and stomatal conductance. Consequently, the whole dry biomass of the plants decreased. The results show that contamination in hydroponic conditions had an irreversible effect on plant fitness due to direct contact between the roots and contaminated solutions.